2014
DOI: 10.1016/j.apt.2013.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-assisted synthesis of Sn nanoparticles via solution plasma technique

Abstract: We have adopted a solution plasma synthesis for preparing Sn nanoparticles (Sn-NPs) directly from metallic Sn electrode. The Sn-NPs were synthesized in the presence of the surfactant, cetyltrimethylammonium bromide (CTAB), and the effect of the concentration of CTAB on the Sn-NPs was investigated. Without CTAB addition, SnO plates were precipitated. Sn-NPs with less than 200 nm were synthesized at a high concentration of 200 × 10 -6 g·ml -1 of CTAB. Electrochemical properties of SnO plates and Sn-NPs were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…4 shows a fast Fourier transform (FFT) image of a single crystal of Sn. Comparing these results with results from the literature [10,17], we concluded that it was possible to obtain a narrower particle size dispersion (from 3 to 5 nm) using pulsed plasma in liquid, as well as high purity and crystallinity. Table 2 shows the particle size data extracted from the TEM results, and gives a comparison with the size of Sn nanoparticles synthesized by other methods [17,[29][30][31].…”
Section: Photocatalytic Measurementssupporting
confidence: 74%
See 2 more Smart Citations
“…4 shows a fast Fourier transform (FFT) image of a single crystal of Sn. Comparing these results with results from the literature [10,17], we concluded that it was possible to obtain a narrower particle size dispersion (from 3 to 5 nm) using pulsed plasma in liquid, as well as high purity and crystallinity. Table 2 shows the particle size data extracted from the TEM results, and gives a comparison with the size of Sn nanoparticles synthesized by other methods [17,[29][30][31].…”
Section: Photocatalytic Measurementssupporting
confidence: 74%
“…Comparing these results with results from the literature [10,17], we concluded that it was possible to obtain a narrower particle size dispersion (from 3 to 5 nm) using pulsed plasma in liquid, as well as high purity and crystallinity. Table 2 shows the particle size data extracted from the TEM results, and gives a comparison with the size of Sn nanoparticles synthesized by other methods [17,[29][30][31]. The particle sizes calculated from XRD data using the Scherer equation were larger than those calculated from the TEM images, because the powder samples used in the XRD analysis were prepared without any additional treatments.…”
Section: Photocatalytic Measurementssupporting
confidence: 74%
See 1 more Smart Citation
“…1, 2 Many novel anode materials have been explored for higher specific capacity and better cycling performance, such as carbonaceous materials, [3][4][5] silicon, 6,7 tin, 8,9 metal oxides, [10][11][12][13][14][15] and so on. Among them, carbonaceous materials have demonstrated to be the most promising and common anode materials for LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to the arc discharge, the current was relatively small under a high voltage. Since lower current led to a decrease in electrode temperature, the Sn nanoparticles were produced using CGDE to improve the capacity of LIBs [22,23]. In this study, we investigated the effect of the electrolyte and the applied voltage on the product in order to fabricate smaller Si-NPs by solution plasma with CGDE.…”
Section: Introductionmentioning
confidence: 99%